Preference to purchase entrance tickets online: a case study of Escape Park, Penang / Khor Poy Hua ... [et al.] - Khor, Poy Hua; Abdul Wahab, Nur Dinie Mustaqim; Lim, Khong Chiu (Universiti Teknologi MARA, Kedah, 2021)
Today, websites are the heart and core of every modern business. It has developed into a typical source of information on data, communication, and shopping. It is increasingly used to gain information and understanding of a topic. Understanding the web surfers' behavior and preferences allows the sports tourism providers to strategize their e-retailing businesses effectively. This study determines the sports tourist's preference to purchase Escape Park entrance tickets online, specifically between the gender groups. Questionnaires were distributed randomly to a total of 192 male and 192 female sports tourists at the ESCAPE Park, Penang. Data collected was statistically analysed using Descriptive Analysis and Independent Sample T-Test. Basically, the sports tourist's decision to purchase entrance ticket online was influenced by the website image, website routine, website knowledge, and website innovativeness. The website image and website routine were described as the utmost influencers on the choice to purchase the e-entrance ticket. Specifically, both male and female sports tourists were equally influence by the factors of website image, website routine, website knowledge, and website innovativeness. These findings can be of reference to e-retail sports tourism researchers and practitioners in planning the upcoming strategies to improve their website page to encourage eretail sports tourism business. Future studies could consider the customer's satisfaction and loyalty for a better understanding of sports tourists' consumer behaviour and focusing on the other demographic elements could benefits comparison purpose.